Roman Rapido - Poe, Fernando Jr; Vela, Helen; Cecilio, Dang
This family saga that spans two decades, from the Japanese Occupation to the 1950s, is adapted for the big scree from the radio serial that went on air in the 1950s.--https://www.imdb.com/title/tt0434311/?ref_=fn_al_tt_1